2012
DOI: 10.2478/v10078-012-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Preference in Gymnastics

Abstract: In gymnastics, most skills incorporate rotations about one or more body axes. At present, the question remains open if factors such as lateral preference and/or vestibulo-spinal asymmetry are related to gymnast’s rotational preference. Therefore, we sought to explore relationships in gymnast’s rotation direction between different gymnastic skills. Furthermore, we sought to explore relationships between rotational preference, lateral preference, and vestibulo-spinal asymmetry. In the experiment n = 30 non-exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…30 seconds). [8][9][10] A valid criticism of this study is the small number of individuals recruited. We hope to recruit a larger cohort of normal participants in the future to strengthen the normative values generated.…”
Section: Discussionmentioning
confidence: 99%
“…30 seconds). [8][9][10] A valid criticism of this study is the small number of individuals recruited. We hope to recruit a larger cohort of normal participants in the future to strengthen the normative values generated.…”
Section: Discussionmentioning
confidence: 99%
“…Takei et al (2000) also found significant relationships to the score in these variables. On vault gymnasts are required to rotate about the longitudinal and the transverse axis in a well-defined manner (Heinen, Jeraj, Vinken, & Velentzas, 2012). Thus an increase in second flight time provides gymnasts with the ability to complete more complex acrobatic skills in the air, increasing the degree of difficulty and the potential for a high score (Bradshaw et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Habacha, Molinaro, Tabben, and Lejeune-Poutrain (2014) hands. In line with this finding, Heinen, Jeraj, Vinken, and Velentzas (2012) investigated male gymnasts with stimuli that were either congruent or incongruent with their rotation preference and found faster RTs for gymnasts in the congruent condition.…”
Section: Introductionmentioning
confidence: 75%
“…A meta-analysis confirmed that the time constraint could influence the performance of mental rotation (Voyer, 2011). According to Heinen et al (2012), adding time constraints would be helpful for observing the effect of sensory-motor experience on cognitive processing. Additionally, in the context of sports, the requirements of movement quality (direction, angle, speed, etc.)…”
Section: Introductionmentioning
confidence: 98%